Recreational drug use among Nigerian university students: Prevalence, correlates and frequency of use - Ajayi, Anthony Idowu; Somefun, Oluwaseyi Dolapo (PLOS ONE, 2020)
Background Given the paucity of data on recreational drug use and the recent media attention on the abuse of drugs such as codeine cough syrups and tramadol, in Nigeria, our study examined the prevalence and frequency of recreational drug use among young adults from two Nigerian universities. We drew from the Socio-ecological Model to examine the influence of factors at the individual and family level on recreational drug use among adolescents and young adults. Methods This cross-sectional study was conducted between February and March 2018 among a final sample of 784 male and female university students selected using stratified random sampling. Binary logistic regression was used to identify significant predictors of ever use and current use of drugs. Results Our analyses showed that 24.5% of students had ever used drugs for recreational purposes, and 17.5% are current users. The median drug use frequency over the past month was six days among current users (n = 137). In the multivariable analyses, living in the same household as one's mother (AOR 0.28 95% CI 0.16–0.49), adequate family support (AOR 0.48 95% CI 0.26–0.89) and frequent attendance of religious fellowships (AOR 0.13 95% CI 0.07–0.25) were significantly associated with a lower likelihood of recreational drug use. However, male sex (AOR 1.52 95% CI 1.05–2.21) was associated with higher odds of recreational drug use. Conclusion The family should be considered as an important unit to sensitize young people on the harmful effects of drug use. It is also vital that religious leaders speak against drug use in their various fellowships. There is a need to address recreational drug use on Nigerian campuses by educating students about its adverse impacts.